Anxiety prevalence and associated factors among frontline nurses following the COVID-19 pandemic: a large-scale cross-sectional study - Wang, Shitao; Luo, Guoshuai; Pan, Dongsheng; Ding, XiangQian; Yang, Fei; Zhu, Liping; Wang, Shuo; Ma, Xuelu (Frontiers in Public Health, 2023)
Introduction: Nurses are more likely to experience anxiety following the coronavirus 2019 epidemic. Anxiety could compromise nurses’ work efficiency and diminish their professional commitment. This study aims to investigate nurses’ anxiety prevalence and related factors following the pandemic in multiple hospitals across China. Methods: An online survey was conducted from April 16 to July 3, 2023, targeting frontline nurses who had actively participated in China. Anxiety and depression symptoms were assessed using the Self-rating Anxiety Scale and the Self-rating Depression Scale (SDS), respectively. Multivariable logistic regression analysis was employed to identify factors linked with anxiety. Results: A total of 2210 frontline nurses participated in the study. Overall, 65.07% of participants displayed clinically significant anxiety symptoms. Multivariable logistic regression revealed that nurses living with their families [2.52(95% CI: 1.68-3.77)] and those with higher SDS scores [1.26(95% CI:1.24-1.29)] faced an elevated risk of anxiety. Conversely, female nurses [0.02(95% CI:0.00-0.90)] and those who had recovered from infection [0.05(95%CI:0.07-0.18)] demonstrated lower rates of anxiety. Discussion: This study highlights the association between SDS score, gender, virus infection, living arrangements and anxiety. Frontline nurses need to be provided with emotional support to prevent anxiety. These insights can guide interventions to protect the mental well-being of frontline nurses in the post-pandemic period.